Plasmacytoid dendritic cells promote rotavirus-induced human and murine B cell responses - Deal, Emily M. (American Society for Clinical Investigation, 2013)
B cell–dependent immunity to rotavirus, an important intestinal pathogen, plays a significant role in viral clearance and protects against reinfection. Human in vitro and murine in vivo models of rotavirus infection were used to delineate the role of primary plasmacytoid DCs (pDCs) in initiating B cell responses. Human pDCs were necessary and sufficient for B cell activation induced by rotavirus. Type I IFN recognition by B cells was essential for rotavirus-mediated B cell activation in vitro and murine pDCs and IFN-α/β–mediated B cell activation after in vivo intestinal rotavirus infection. Furthermore, rotavirus-specific serum and mucosal antibody responses were defective in mice lacking functional pDCs at the time of infection. These data demonstrate that optimal B cell activation and virus-specific antibody secretion following mucosal infection were a direct result of pDC-derived type I IFN. Importantly, viral shedding significantly increased in pDC-deficient mice, suggesting that pDC-dependent antibody production influences viral clearance. Thus, mucosal pDCs critically influence the course of rotavirus infection through rotavirus recognition and subsequent IFN production and display powerful adjuvant properties to initiate and enhance humoral immunity.